Niederschlagsverhältnisse und agrarmeteorologische Bedingungen für die Landwirtschaft im Einzugsgebiet des Titicacasees - Schröder, Rudolf (ERDKUNDE, 1981)
The hydrological catchment area of Lake Titicaca, which com prises about 60,000 km2, is of special agro-meteorological significance with its mean annual temperature of 8°C.,since temperature total here is no longer sufficient for most of the more demanding cultivated plants. The region is situated in the zone of summer precipitation of the southern part of the continent. The annual means fluctuate between 500 and 1,000mm, with the highest values ocurring in the vicinity of the lake or on islands. The probability of almost 500 mm falling annually in the vicinity of the lake is about 80 percent. The water supply in the catchment area of the lake is sufficient for cultivation only in the summer rainy season (November to March). All plant development phase occur during this period. The other months produce a negative balance. Since temperatures fall below freezing point on most days between April and October, temperature too imposes a temporal limit for cultivation. Apart from indigenous tuber and root crops, grains and legumes the imported wheat, barley and large field beans are the most important plants cultivated for nutritional purposes, which are able to grow and mature under these extreme conditions.